Diversity, distribution and natural Leishmania infection of sand flies from communities along the Interoceanic Highway in the Southeastern Peruvian Amazon - Valdivia, Hugo O. (2021)
This work was supported by the US DoD Armed Forces Health Surveillance Division and its Global Emerging Infections Surveillance branch (AFHSD/GEIS), PROMIS ID P0143_19_N6_03, 2019-2020. AGL is supported by training grant D43 TW007393 awarded by the Fogarty International Center of the US National Institutes of Health. JGP was supported by FONDECYT-CONCYTEC (grant contract number 100-2016FONDECYT). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.